THE IMPACT OF KNOWLEDGE ON STUDENTS’ TRAFFIC AWARENESS AT JUNIOR HIGH SCHOOLS IN PANGKALAN KURAS DISTRICT - Perestian Ares Sandi; Sudrajat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study investigates the effect of students’ knowledge on traffic awareness among junior high school students at SMP Negeri Sorek Dua, Pangkalan Kuras, Pelalawan, Riau. A quantitative descriptive design was employed using total sampling of 224 students (Grades VII–IX). Data were collected via two Likert-scale questionnaires (16 items for knowledge; 16 items for awareness). Instrument quality was confirmed through item validity testing and reliability analysis (Cronbach’s alpha = 0.873 for knowledge; 0.862 for awareness). Assumption checks indicated normal data distribution and a linear relationship between variables. Descriptively, students’ traffic knowledge was high (mean score = 84.2), and traffic awareness was good (mean score = 81.5). Simple linear regression showed significant and effect of knowledge on traffic awareness. There is 79% of the variance in awareness is explained by knowledge, with the remaining 21% attributable to other factors. These findings highlight the central role of cognitive understanding in shaping safe traffic behavior. Practically, integrating traffic safety content into Social Studies (IPS), coupled with experiential activities (simulations, role-play) and reinforcement through school patrol (PKS), is recommended to transform knowledge into consistent safe practices.